ANALYZING SYLLABLE AND RHYME STRUCTURE OF LAMPUNGNESE WAWANCAN IN TANGGAMUS - Zulyaden; Susanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the phonological aspects of wawancan, a form of Lampung oral literature, focusing on syllable structure and rhyme patterns in the Tanggamus region, where the coastal (Api/A) dialect is used. Employing a qualitative descriptive approach, the data were collected from fifteen wawancan performances and analyzed to identify and classify their syllabic and rhyming structures. The findings reveal five primary syllable structures: V, VC, CV, CVV, and CVC, with the CV pattern being the most dominant, indicating a preference for open syllables in the Lampung language. The distribution of syllable structures across word positions reflects phonotactic constraints consistent with the Maximal Onset Principle. In terms of rhyme, the results show that half rhyme, particularly assonance, is the most frequently used form, followed by full rhyme, while rich rhyme occurs only marginally. The dominant rhyme scheme identified is abab, with occasional use of aaaa and abcabc. Additionally, masculine rhyme appears more frequently than feminine and triple rhymes, suggesting a tendency toward simpler rhyming patterns. Overall, this study highlights the significance of phonological features in shaping the aesthetic and communicative functions of wawancan. The findings contribute to the documentation and preservation of Lampung oral traditions and provide insights into the linguistic characteristics of the Lampung language.